2007
DOI: 10.1080/13548500600731708
|View full text |Cite
|
Sign up to set email alerts
|

Parental reports of emotional and behavioural difficulties on the SDQ for school-age children with vertically acquired HIV infection living in London

Abstract: This study uses a screening questionnaire (the Strengths and Difficulties Questionnaire, SDQ) to indicate levels of parental or carer concern about behavioural or emotional difficulties in a representative group of school-age children with vertically acquired HIV attending London clinics. Fourteen per cent of the total 107 children screened were reported to have behavioural and emotional difficulties scoring in the "abnormal" range. Older children tended to have higher scores. Overall, levels of reported diffi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
16
2
1

Year Published

2010
2010
2024
2024

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 19 publications
(20 citation statements)
references
References 15 publications
(23 reference statements)
1
16
2
1
Order By: Relevance
“…The age finding is consistent with that of Bachanas et al (2001) who found younger children had more externalizing behavior problems than older children (although age in their sample ranged between 6 and 16). Our findings were inconsistent with Melvin et al's (2007) who found older children were reported with higher scores on this measure. Again their sample was younger than the current sample (age range was between 5 and 16).…”
Section: Discussioncontrasting
confidence: 81%
See 3 more Smart Citations
“…The age finding is consistent with that of Bachanas et al (2001) who found younger children had more externalizing behavior problems than older children (although age in their sample ranged between 6 and 16). Our findings were inconsistent with Melvin et al's (2007) who found older children were reported with higher scores on this measure. Again their sample was younger than the current sample (age range was between 5 and 16).…”
Section: Discussioncontrasting
confidence: 81%
“…This was not the case. The inconsistent findings between Melvin et al's (2007) study and ours (despite the similar ethnicity and clinic context) may be related to the difference in informants (carer vs. self-report). Although inter-informant reliability has been reported to be high for the SDQ (Goodman, Meltzer, & Bailey, 2003;Muris, Meesters, & Van den Berg, 2003) significant discrepancies between different informants have been reported elsewhere (Bachanas et al, 2001;Madden, Hastings, & V'ant Hoff, 2002).…”
Section: Discussioncontrasting
confidence: 73%
See 2 more Smart Citations
“…Psychosocial dysfunction and behavior problems have been identified in HIV positive school aged children in varying percentages, ranging from as high as 80.7% to 14%. 18,23 But there have been some contradictory reports which state that psychological adjustment scores were not significantly different in the HIV and demographically matched healthy control groups. 24 In some instances, HIV infected children were reported to have been experiencing low levels of depressive and anxious affect and they generally felt positively about themselves.…”
Section: Duration Of Illnessmentioning
confidence: 91%